Contemporary Proton Therapy Systems Adequately Protect Patients from Exposure to Stray Radiation - Newhauser, Wayne D. (2009)
Proton beam therapy has provided safe and effective treatments for a variety of adult cancers. In recent years, there has been increasing interest in utilizing proton therapy for pediatric cancers because it allows better sparing of healthy tissues. Minimizing exposures of normal tissues is especially important in children because they are highly susceptible to consequential late effects, including the development of a radiogenic second cancer, which may occur years or even decades after treatment of the first cancer. While the dosimetric advantage of therapeutic proton beams is well understood, relatively little attention has been paid to the whole-body exposure to stray neutron radiation that is inherent in proton therapy. In this report, we review the physical processes that lead to neutron exposures, discuss the potential for mitigating these exposures using advanced proton beam delivery systems, and present a comparative analysis of predicted second cancer incidence following various external beam therapies. In addition, we discuss uncertainties in the relative biological effectiveness of neutrons for carcinogenesis and the impact that these uncertainties have on second-cancer risk predictions for survivors of adult and childhood cancer who receive proton therapy.